1997
DOI: 10.1021/ja962439q
|View full text |Cite
|
Sign up to set email alerts
|

High Sensitivity and Fragmentation Specificity in the Analysis of Drug−DNA Adducts by Electrospray Tandem Mass Spectrometry

Abstract: DNA alkylation is a key cellular event in the mechanism of action of clinical anticancer drugs, chemical mutagens, and carcinogens. 1 The nitrogen and oxygen atoms of purines are preferentially alkylated, with the affinity for a particular base depending on the sequence of neighboring bases. It is most likely that the sequence selectivity of the agent is important in determining the nature of the biological response. 2 Methods based on molecular biology have been used extensively to determine the sequence sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
48
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 40 publications
3
48
0
Order By: Relevance
“…The product-ion spectrum of the [M Ϫ H] Ϫ from T3X (Table 1, X ϭ abasic site) is considerably simpler than that of the corresponding unmodified ODN, as was noted for abasic sites produced in mass spectrometric fragmentation [15,16]. The precursor containing the abasic site gives only the w 3 ' ion at the abasic site, revealing its location (Figure 1) (we use the prime notation for the fragments as a convenience to distinguish the abasic ODNs).…”
Section: Location Of the Abasic Sites In Model Odns By Esi Ms/msmentioning
confidence: 88%
See 1 more Smart Citation
“…The product-ion spectrum of the [M Ϫ H] Ϫ from T3X (Table 1, X ϭ abasic site) is considerably simpler than that of the corresponding unmodified ODN, as was noted for abasic sites produced in mass spectrometric fragmentation [15,16]. The precursor containing the abasic site gives only the w 3 ' ion at the abasic site, revealing its location (Figure 1) (we use the prime notation for the fragments as a convenience to distinguish the abasic ODNs).…”
Section: Location Of the Abasic Sites In Model Odns By Esi Ms/msmentioning
confidence: 88%
“…Vouros and coworkers [15] also reported a similar method to identify and locate an aflatoxin B 1 modified guanine in three isomeric ODN 9-mers. The latter work of Vouros [15] and that of Sheil's groups [16] demonstrated the simple and informative decomposition reactions of abasic sites produced after loss of a base in a mass spectrometric fragmentation. To our knowledge, no one has systematically studied the fragmentation of ODNs bearing "natural" abasic sites (i.e., sites in which the nucleobase reacts in solution and is replaced with an OH group).…”
mentioning
confidence: 97%
“…During the last decade the development of electrospray ionisation mass spectrometry (ESI-MS) has allowed accurate mass measurements to be performed on relatively large oligonucleotides including plasmid DNA. [15][16][17][18][19] ESI-MS has also been used for the characterisation of covalent [20][21][22][23][24] and non-covalent [25][26][27][28] drug-DNA complexes. For example, ESI-MS studies on DNA bound to the antibiotic hedamycin revealed that the drug selectively binds to specific DNA sequences and significantly increased the stability of duplex DNA in the gas phase.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, mass spectrometry has been employed directly or coupled with high-performance separation techniques to characterize a variety of covalent adducts produced by alkylation of nucleic acids in vivo and in vitro [11][12][13][14][15][16][17][18][19]. The combination of direct infusion electrospray ionization (ESI) [20] and Fourier transform mass spectrometry (FTMS) [21] constitutes an ideal platform for the analysis of this type of samples, which affords the benefits of high mass accuracy and resolving power [22].…”
mentioning
confidence: 99%